# Which of the Following Represents the Zeros of f(x) = x^{3} − 3x^{2} − 2x + 6?

We will be simplifying the equation to solve it.

## Answer: The Zeros of the Equation f(x) = x^{3} − 3x^{2} − 2x + 6 are 3, √2, and -√2

Let's solve this step by step to find the zeros of f(x) = x^{3} − 3x^{2} − 2x + 6.

**Explanation:**

Given that, f(x) = x^{3} − 3x^{2} − 2x + 6

We have to find the roots of the equation.

f(x) = x^{3} − 3x^{2} − 2x + 6

= x^{2}(x − 3) − 2(x - 3)

= (x^{2 }- 2) (x − 3)

x - 3 = 0 and (x^{2 }- 2) = 0

x = 3 and x^{2 }= 2

x = 3 and x^{2 }= √2, -√2

You can verify your answer using Cuemath's Roots Calculator.